O apelo afetivo nas estratégias narrativas audiovisuais do Exército Brasileiro. - Soares, Danilo Gomes Guerra (2020)
The present dissertation starts from an analytical principle in the narrative aesthetics of the Brazilian Army 's audiovisual productions. With the intention of entering and implanting military values in the various forms of narration, we identify possibilities to innovate the standards that follow their current videos. We have found a way to modify these productions in a more creative way, with theoretical basis in the dramatic and cinematographic narratives. We believe that for effective communication, affectivity is the ideal propellant, as a way to impact the recipient emotionally. Roberts (2005) argues that 80% of our decisions are made through emotions. In order to analyze affective appeals and their possible propagation, the focus of this project is to study the emotions and their needs in audiovisual and cinematographic narratives, based on the concepts of Affective Economy, Lovemarks, Storytelling and affectivity in spectatorial reception. For imagery, war films with military emotive appeal were analyzed in order to raise criteria and narrative elements, respecting the transmediational character of the cinema for the TV and internet pieces. The main objective of this work is to analyze and develop narrative strategies to be applied in video production prototypes for a Brazilian Army (EB) campaign aimed at reaching young people between 16 and 22 years old, adhering to the emotions linked to military values. It is assumed that the EB requires a greater institutional understanding and the propagability of the Earth Force and that, in view of this, it will have better institutional results if presented to the young citizen, narrative strategies loaded with affectivity and identification without loss of military values, based on the genre of war movies. We also assume that the concepts listed here can contribute to other institutions that aim to impact their audience affectively.